Impairment of Uterine Contractility Is Associated with Unexplained Infertility - Hunt, Sarah; Abdallah, Karim S.; Ng, Ernest; Rombauts, Luk; Vollenhoven, Beverley; Mol, Ben W. (Seminars in Reproductive Medicine, 2020)
The uterine junctional zone represents the juncture between endometrium and myometrium. The junctional zone is hormonally dependent and displays continuous peristaltic activity throughout the menstrual cycle in the nonpregnant state which is concerned with sperm transport and embryo implantation. Peristalsis may be observed using various invasive and noninvasive modalities, of which ultrasound is the most readily applied in the clinical setting. Women with pelvic pathology display alterations in uterine peristalsis which may contribute to infertility. Characterization of peristalsis in infertility subgroups, the development of a subjective peristalsis tool, and the application of potential therapeutics to an assisted reproductive treatment setting are the subject of ongoing investigation. Meta-analysis indicates a potential role for oxytocin antagonist in the improvement of fertility treatments.
Keywords: endometrial myometrial junction; uterine junctional zone; endometrial contractions; uterine peristalsis